The effect of transfer funds to regions and village funds on human development index in districts of west java province in 2015-2018 - Muhammad Afrizal Yusuf; Arif Afendi (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - This research aims to analyze the influence of the Revenue Sharing Fund, General Allocation Fund, Special Allocation Fund, and Village Fund on the level of Human Development Index in 18 Districts in West Java Province in 2015-2018.Method - The data used in this study were secondary. The Revenue Sharing Fund, General Allocation Fund, Special Allocation Fund, and Village Fund are obtained from the Central Government Financial Report from the Ministry of Finance. Meanwhile, the human development index data were obtained from the Central Bureau of Statistics (BPS). The data were analyzed using multiple linear regressions.  Result - The results showed that the revenue sharing fund had a positive and significant effect on the Human Development Index, the general allocation fund had a negative and significant effect on the human development index, the special allocation fund had a positive but insignificant effect on the human development index, while the village fund had a negative and insignificant effect on the human development index.Implication - This study provides information that in the implementation of effective transfers of funds in the process of receiving or transferring funds from provinces to regions, certainty and clarity regarding expenditure burdens or authority is needed which is a prerequisite for the successful implementation of fiscal decentralization policies through fund transfers so that an increase in the human development index can be achieved.Originality - By using secondary data from a sample of districts and cities in West Java, this study illustrates how the influence of Transfer Funds to Regions and Village Funds in increasing the Human Development Index.